2020
DOI: 10.1002/14651858.cd012681.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Severe fatigue after treatment for childhood cancer

Abstract: BackgroundTreatment strategies for childhood cancer are improving, resulting in higher survival rates. However, the consequences of childhood cancer do not end with the successful completion of cancer treatment. Most patients will develop late e ects a er cessation of treatment. Severe fatigue is seen as a common and debilitating late e ect in cancer survivors. Although most research on fatigue has been performed in patients a er adult-onset cancer, our review focuses on fatigue a er childhood cancer. Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 147 publications
3
50
0
2
Order By: Relevance
“…ESs for fatigue in the young adult group may be due to longer time since treatment completion, with initial symptoms of fatigue having subsided with time. This is consistent with previous findings showing that although there is a subgroup for whom symptoms may persist several years upon treatment completion, in many PBT survivors fatigue reduces posttreatment (Boonstra et al, 2017;Brand et al, 2016;Clanton et al, 2011;Mulrooney et al, 2008;van Deuren et al, 2020).…”
Section: Ef Complaints Vs Reports Of Psychological Problems and Fatisupporting
confidence: 92%
See 2 more Smart Citations
“…ESs for fatigue in the young adult group may be due to longer time since treatment completion, with initial symptoms of fatigue having subsided with time. This is consistent with previous findings showing that although there is a subgroup for whom symptoms may persist several years upon treatment completion, in many PBT survivors fatigue reduces posttreatment (Boonstra et al, 2017;Brand et al, 2016;Clanton et al, 2011;Mulrooney et al, 2008;van Deuren et al, 2020).…”
Section: Ef Complaints Vs Reports Of Psychological Problems and Fatisupporting
confidence: 92%
“…One of most frequent and debilitating late effects following PBT treatment is excessive fatigue (van Deuren et al, 2020). Fatigue refers to the persistent, subjective experience of physical, emotional, and/or cognitive tiredness and lack of energy, not proportional to recent activity, and interfering with usual functioning (Bower, 2014;Zeller et al, 2014).…”
Section: Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…While some studies indicate that fatigue is a problem among (YA)CCS [18,20], other studies show that fatigue levels among CCS do not differ from reference groups or that clinical significance is questionable [24,25]. A recent review concluded that the prevalence of severe fatigue among CCS remains unclear, due in part to the heterogeneity of studies regarding inclusion criteria and samples as well as the questionnaires used to assess fatigue [26]. As fatigue has previously been linked to poor (HR)QOL [5,18,27], it is crucial to investigate the incidence of fatigue in the Dutch population of YACCS and explore underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Childhood cancer patients face additional health risks due to exposure to radiation and chemotherapy during early life growth and development. Recent literature reviews reported the following late adverse effects childhood cancer: increased risk of subsequent primary malignancies, hypothyroidism, severe fatigue, hearing loss organ dysfunctions (ovarian, liver, lungs, heart, kidney and bladder), obesity as well as musculoskeletal, dental and psychosocial effects [15][16][17][18][19][20][21]. The Australian healthcare system consists of both public and private providers.…”
Section: Introductionmentioning
confidence: 99%